Relaksasi Otot Progresif dan Slow Deep Breathing Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi - Anggraini, Devita Anugrah; Al Khasanah, Adhin; Ambarsari, Tika (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The World Health Organization (WHO) states that as many as 972 million people or 26.4% of the world's population suffer from hypertension. Complications of hypertension cause heart disease, stroke and kidney disease. One non-pharmacological therapy is progressive muscle relaxation and slow deep breathing. This research design uses a pre-experimental one group pre-test post-test design. Sampling in this study used a purposive sampling technique of 45 respondents. The results of analysis using the paired t-test showed that systolic and diastolic blood pressure showed a significant decrease before and after the combined intervention of progressive muscle relaxation and slow deep breathing where the p-value before the therapy was given = 0.000 and the p-value after the intervention was given = 0.000 (α <0.05). There is an influence between the combination of progressive muscle relaxation and slow deep breathing on reducing blood pressure in hypertensive sufferers.